Brewing Science: A Multidisciplinary Approach - Mosher, Michael; Trantham, Kenneth; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2017)
This text finally collects all the introductory aspects of beer brewing science into one place for undergraduate brewing science courses. This expansive and detailed work is written in conversational style, walking students through all the brewing basics from the origin and history of beer to the brewing process to post-brew packaging and quality control and assurance. As an introductory text, this book assumes the reader has no prior knowledge of brewing science and only limited experience with chemistry, biology and physics. The text provides students with all the necessary details of brewing science using a multidisciplinary approach, with a thorough and well-defined program of in-chapter and end-of-chapter problems. As students solve these problems, they will learn how scientists think about beer and brewing and develop a critical thinking approach to addressing concerns in brewing science. As a truly comprehensive introduction to brewing science, Brewing Science: A Multidisciplinary Approach walks students through the entire spectrum of the brewing process. The different styles of beer, the molecular makeup and physical parameters, and how those are modified to provide different flavors are listed. All aspects of the brewery process, from the different setup styles to sterility to the presentation of the final product, are outlined in full. All the important brewing steps and techniques are covered in meticulous detail, including malting, mashing, boiling, fermenting and conditioning. Bringing the brewing process full circle, this text covers packaging aspects for the final product as well, focusing on everything from packaging technology to quality control. Students are also pointed to the future, with coverage of emerging flavor profiles, styles and brewing methods. Each chapter in this textbook includes a sample of related laboratory exercises designed to develop a student's capability to critically think about brewing science. These exercises assume that the student has limited or no previous experience in the laboratory. The tasks outlined explore key topics in each chapter based on typical analyses that may be performed in the brewery. Such exposure to the laboratory portion of a course of study will significantly aid those students interested in a career in brewing science.
Introduction to Brewing Science -- Beer Styles -- Molecules and Other Matters -- Overview of the Brewing Process -- The Food for the Brew -- Mashing -- Sparging -- Wort Boiling -- Cooling and Fermenting -- Conditioning -- Packaging -- Quality Assurance and Quality Control -- Appendix A -- Appendix B.
Keywords: Food science; Chemistry, Organic; Food Science; Organic Chemistry